Non-Linear Abelian Scenarios and Yang-Mills Theory - Sousa, Saulo Machado Moreira; Soares, I.; Leite, D.; Doria, R. M. (JOURNAL OF ADVANCES IN PHYSICS, 2017)
We present a natural formulation for constructing Yang-Mills theories from the incorporation of non-linearities to the Maxwell’s theory of electromagnetism. Our formulation is strongly based on Noether’s Theorem and aims to show how the introduction of non-linearities can turn a global invariance into a local symmetry as the more general Yang-Mills type of symmetry.